Pelatihan Membuat Masker dengan Hiasan Sulam Benang untuk Ibu-ibu dan Remaja Putri di Tengah Pandemi Covid-19 - Hellen Last Fitriani; Sukma Erni; Salmiah (Tasnim Journal for Community Service, 2021)
This community service activity aims to: 1) develop the knowledge possessed by the servant; 2) find solutions to problems that exist in society; 3) create creativity that is useful for members of the Pekanbaru community; and 4) making the basic material of broken cloth into a variant of creative masks that can improve the family's economy. The strategic targets in this service are the mothers and young women of the Pekanbaru Riau community. In order to achieve this, the servant takes the following steps: 1) contacting Mrs. Rima from the Creative Children's Gallery as a resource person; 2) share information with the public for those who are willing to take part in the training; 3) create a Wa Group to share information about training; 4) conduct meetings via zoom meeting; 5) explanation of making embroidered cloth masks through creative videos shared by resource persons; 6) the community is given the opportunity to make embroidered cloth masks according to the video stages that are distributed through their respective homes; 7) people are given 1 week to make embroidered cloth masks; 8) the community shares their work through Group Wa; and 9) resource persons provide feedback and direction on the work of mothers and young women. The results of the service produce creative mask variants that can improve the family's economy from the basic ingredients of broken cloth.